The Inheritance of Human Traits in the Qurâ€™an Based on the Scientific Interpretation of ZaghlÅ«l RÄghib Muá¸¥ammad an-NajjÄr - Arib, Juhrah M.; Khairiyah, Nikmatul; Suryadinata, M.; Mokodenseho, Sabil (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
This article aims to analyze the inheritance of human traits in the Qurâ€™an, specifically at Surah An-Nisa verse 1, based on the scientific interpretation of ZaghlÅ«l an-NajjÄr. This study discusses ZaghlÅ«l an-NajjÄr because he is a geologist and Muslim scholar who has written many books related to science in the Qurâ€™an. The type of this study was qualitative research with a descriptive method. Primary data were obtained through library research related to the works of an-NajjÄr and interpretations of the Qurâ€™an and hadith, while articles and books were used as secondary data. The employed research approaches were the character approach to study the history, ideas, and socio-historical conditions of ZaghlÅ«l an-NajjÄr, the exegesis approach to study the content of the Qurâ€™an, and the scientific approach to understand and reveal the meaning of the verses of the Qurâ€™an. This study concludes that the inheritance of human traits in the Q.S. An-Nisaâ€™ verse 1 according to ZaghlÅ«l an-NajjÄr is in the words â€œal-nafs al-wÄá¸¥idahâ€ (one soul), which means all humans come from the first created creatures, namely Adam. Likewise, the creation of Eve is explained in the words â€œwa khalaqa minhÄ zaujahÄâ€ (and We created his wife from himself).